Forebrain Network Associated With Cardiovascular Control in Exercising Humans. Issue 4 (17th October 2022) - Shoemaker, J. Kevin
Abstract : This article describes the forebrain neurocircuitry associated with rapid heart rate response at the exercise onset with attention to ascending somatosensory information from the Type I and II afferents from the contracting muscle and potential influence of sensory information related to blood pressure and changes in heart rate. Abstract : This article describes the forebrain neurocircuitry associated with rapid heart rate response at the exercise onset with attention to ascending somatosensory information from the Type I and II afferents from the contracting muscle and potential influence of sensory information related to blood pressure and changes in heart rate.